Best practices for the research doctorate? A case for quality and success in knowledge production - Bitzer, Eli M (South African Journal of Higher Education, 2016)
The contribution of research doctoral degrees to knowledge production in processes of national and international economic and social advancement seems substantial. As candidates and their supervisors carry huge responsibilities in conducting and supervising doctoral research, the quality and success of these studies are associated with an array of factors or challenges. This article explores some of these challenges and proposes that a set of universal standards in the form of guidelines for ‘best practices’ may possibly contribute to doctoral research of quality associated with success. It also suggests that doctoral studies might contribute even more substantially to the quality of knowledge production if quality measures are taken into account by institutions that award doctoral degrees and research-intensive universities in particular. Key words: Doctoral success; Doctoral quality; Doctoral standards; Knowledge production; Postgraduate studies; Best practices.